A time-calibrated ‘Tree of Life’ of aquatic insects for knitting historical patterns of evolution and measuring extant phylogenetic biodiversity across the world - García-Girón, Jorge; Múrria, Cesc; Arnedo, Miquel A.; Bonada, Núria; Cañedo-Argüelles, Miguel; Derka, Tomáš; Fernández-Calero, Jose María; Li, Zhengfei; Tierno de Figueroa, José Manuel; Xie, Zhicai; Heino, Jani (Earth-Science Reviews, 2024)
The extent to which the sequence and timing of important events on Earth have influenced biological evolution through geological time is a matter of ongoing debate. In this context, the phylogenetic history of aquatic insects remains largely elusive, and our understanding of their chronology is fragmentary and incomplete at best. Here, after gathering a comprehensive data matrix of 3125 targeted rRNA and protein-coding gene sequences from nine independent gene portions, we built a well-supported time-calibrated phylogenetic tree comprising almost 1200 genera that represent a large proportion of extant families of dragonflies and damselflies (Odonata), mayflies (Ephemeroptera), stoneflies (Plecoptera), and caddisflies (Trichoptera). We reviewed the main evolutionary and historical scenarios for each aquatic insect lineage as revealed by our best-scoring molecular tree topology, major ancient radiations, calibrated divergence estimates, and important events in geological history related to the spatial arrangement of land masses, continental drift, and mass extinctions. Molecular dating using the birth-death model of speciation, with a lognormal-relaxed model of sequence evolution informed by transcriptomic constraints, suggested that (i) dragonflies and damselflies first radiated approximately 220 million years (Ma) ago and most extant lineages thrived independently after the Triassic–Jurassic (Tr–J) extinction event; (ii) mayflies underwent bursts of diversification during the Cretaceous; (iii) ancestral divergence separating the stonefly suborders Arctoperlaria and Antarctoperlaria was consistent with geographical isolation after vicariant fragmentation and tectonic splitting of the supercontinent Pangaea around 170 Ma ago; and (iv) the most recent common ancestors of caddisflies extended back to the time of Pangaea, supporting the earliest offshoot of the ‘retreat-making’ Annulipalpia and a sister relationship between the predatory free-living Rhyacophilidae and Hydrobiosidae. Our ‘Tree of Life’ of aquatic ...